Pricing for finished products of the enterprise: accounting and analytical aspect - Правдюк, Наталія Леонідівна (Problems of Theory and Methodology of Accounting, Control and Analysis, 2017)
The pricing policy chosen by the enterprise in respect of goods and finished products of own production, has a decisive influence on the formation of financial results. In modern economic conditions we need to strengthen managerial decisions on the choice and carrying out price policy and a means of solving this problem is accounting. To determine the boundaries and competence of decision-making we analyzed the regulation of these terms and processes, as well as the dynamics of the stocks across sectors of the economy, the consumer price index, producer price index, the price index of realization of industrial products. Widely used data analytical reviews of the national Bank of Ukraine, enterprises' expectations regarding efficiency, the analysis of financial market indicators, etc. Established that the provision of information management pricing of goods shall conform to the requirements of the economy, by deepening complexity of accounting, to ensure the needs of consumers. According to the study substantiates the basics of accounting and analytical aspect of the pricing policy for finished products businesses. In the study of pricing policies in respect of goods in accounting and analytical aspect, we have established the following. The existing normative-legal acts and definitions of researchers on economic and accounting analysis of the concept give a sufficiently wide interpretation, which depends on the orientation and activity of the enterprise. Factors and points of influence on the efficiency of the pricing policy are: information support of process of pricing assessment of pricing factors, establish the objectives of price policy, assessment of customer demand, cost analysis, competition analysis, selecting a pricing method that measures the price adjustment, the evaluation price risk. The economic impact of the market environment is the most significant to the pricing policy of agricultural enterprises, which revealed the analysis of the dynamics and price ratios in the economy in General and the agricultural sector, a manifestation of which is the periodic appearance of price spikes in the markets of food products and agricultural products. Accounting and analytical management of pricing policy on finished products of the enterprise is reduced to the following algorithm: the block of forming of information on the costs of production (base prices); block the formation of the information concerning costs of sale; creative analytical aspect of price policy – the price of profit; analysis and correction of information about a possible sale price for their own products according to the fair value of similar products on the market. Prospects for further research in this direction is development of methodical recommendations for accounting of transactions that form the pricing policy in respect of finished products, standardization and automation of this process and promoting it.